(untitled) (Journal of Social Sciences Review, 2023)
The research aimed to an assessment of the Information and Communication Technology (ICT) competencies of medical librarians in the province of Punjab. The research study was descriptive in nature, and a quantitative approach was used for which a closed-ended questionnaire was conducted from librarians working in different health institutions in Punjab province. Therefore a whole population sample of 62 health institutions of the public and private sectors was selected from the areas of Punjab. A questionnaire consisted of two types of questions, one five rating Likert scale and the other yes and no type questions. Collected data was analyzed considering the objectives and research questions of the study. Descriptive statistics were used for data analysis which includes frequency, percentage, mean score and standard deviation for item analysis. It was found that there was a lack of training courses in medical librarianship. Therefore, it is recommended that the intuitions may demand training courses in medical librarianship, and the government may support and provide funds to arrange training. Medical institutions do not have sufficient funds. This factor caused a hindrance in the proper functioning of and enhancing their competencies in the field of ICT to keep libraries updated to fulfil the need of the day, so the government and the institutions may provide sufficient funds to the concerned field of libraries.